2010
DOI: 10.1002/jcp.22188
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo organ culture of adipose tissue for in situ mobilization of adipose‐derived stem cells and defining the stem cell niche

Abstract: In spite of the advances in the knowledge of adipose-derived stem cells (ASCs), in situ location of ASCs and the niche component of adipose tissue (AT) remain controversial due to the lack of an appropriate culture system. Here we describe a fibrin matrix-supported three-dimensional (3D) organ culture system for AT which sustains the ASC niche and allows for in situ mobilization and expansion of ASCs in vitro. AT fragments were completely encapsulated within the fibrin matrix and cultured under dynamic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…ASCs and BMSCs are similar in the expression of surface markers according to our study as well as previously published reports (7)(8)(9)29). Specifically, we found CD34, a surface marker of hematopoietic cells, negative or weakly positive, in both ASCs (8.23%) and BMSCs (10.13%), whereas CD146, a surface marker of mesenchymal stem cells, was positive in both (64.22% and 76.03%), implying a shared origin of ASCs and BMSCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ASCs and BMSCs are similar in the expression of surface markers according to our study as well as previously published reports (7)(8)(9)29). Specifically, we found CD34, a surface marker of hematopoietic cells, negative or weakly positive, in both ASCs (8.23%) and BMSCs (10.13%), whereas CD146, a surface marker of mesenchymal stem cells, was positive in both (64.22% and 76.03%), implying a shared origin of ASCs and BMSCs.…”
Section: Discussionsupporting
confidence: 92%
“…Cai et al reported that BMSCs and ASCs were both smooth muscle actin (SMA) positive pericytes (7)(8), which agrees with Yang et al 's results that ASCs were CD34 negative and SMA positive, and belonged to a subset of pericytes (9). On the other hand, Lin et al claimed ASCs were CD34 posi-tive and SMA negative and thus, were not pericytes (10).…”
Section: Introductionmentioning
confidence: 56%
“…However, perivascular cells produce angiogenic factors such as basic fibroblast growth factor, heparin binding-epidermal growth factor-like growth factor (HB-EGE), keratinocyte growth factor, and vascular endothelial growth factor [25] and have the ability to organize blood vessel development from the host endothelial cells [46,47]. On the basis of published results and our own knowledge, perivascular cells promote angiogenesis via secretion of angiogenic factors or by recruiting domestic endothelial cells but are less likely to trans-differentiate into endothelial cells.…”
mentioning
confidence: 99%
“…However, initial in situ OCs shared the typical immunophenotypic profiles with CSCs, while the outgrowth of committed cardiac cells was rarely observed or absent. Similar to the myocardium, both adipose and loose connective tissues are also comprised of committed cells, such as microvascular ECs and vSMCs, fibroblasts as well as tissue-resident MSCs [18,20]. However, our previous studies indicated that fibrin-supported organ cultures showed the selective enrichment of tissue-resident MSCs from adipose and loose connective tissues, but limited or absent committed cell outgrowth.…”
Section: Discussionmentioning
confidence: 98%